MAP2K1-Mutated Melanocytic Neoplasms With a SPARK-Like Morphology - Donati, Michele; Nosek, Daniel; Waldenbäck, Pia; Martinek, Petr; Jonsson, Björn-Anders; Galgonkova, Petra; Hawawrehova, Marcela; Berouskova, Petra; Kastnerova, Liubov; Persichetti, Paolo; Crescenzi, Anna; Michal, Michal; et al. (The American Journal of dermatopathology, 2021)
Specific alterations involving MAPK genes (MAP3K8 fusions, MAP3K3 fusions) have been recently detected in a subgroup of spitzoid neoplasms that seem to constitute a distinctive clinicopathologic group, occur mostly in younger patients (median age 18 years) and present with atypical histologic features associated with frequent homozygous deletion of CDKN2A, qualifying a high proportion of them as Spitz melanoma (malignant Spitz tumor). Apart from lesions with spitzoid morphology harboring MAP3K8 or MAP3K3 fusion, a single case with MAP2K1 deletion has been identified. The authors report herein 4 melanocytic lesions with a MAP2K1 mutation, all showing similar microscopic appearances, including spitzoid cytology and dysplastic architectural features, resembling so-called SPARK nevus, suggesting that these lesions may represent another distinctive group.
Keywords: Nevus, Epithelioid and Spindle Cell; epiteloidní a vřetenobuněčný névus; Melanoma; Middle Aged; mužské pohlaví; ženské pohlaví; MAP kinasa-kinasa 1; melanom; dospělí; Humans; MAP Kinase Kinase 1; Adult; nádory kůže; Female; Skin Neoplasms; lidé; Male; lidé středního věku